Problems of the activity of the maritime transport system of Ukraine in the conditions of globalization of the world maritime complex - Golinskiy , V.V. (Theory and Practice of Public Administration, 2019)
The main issue of the maritime transport system is discussed in the article. The problem is described by the facts of the low intensity of the processes of transformation of the maritime transport system of Ukraine into the global logistical-coordination system of the world.The purpose of the paper is to elucidate the positions and approaches to solving public management issues of the functioning of the maritime transport system of Ukraine. Also, the purpose is connected with the study of changes in the management systems of transport infrastructure on a global scale.Currently, 18 sea trading ports operate on the Black Sea and Azov coast of Ukraine. 4 seaports are the largest - Odesa, Chornomorsk, Southern and Mykolaiv. Their total capacity is about 180 million tons. But in the world ranking of port quality, calculated by the World Economic Forum, Ukraine has moved from 107 to 93 in 137 countries.The dynamics of the development of marine infrastructure shapes the state of the economy. But in Ukraine, the indicators of the economy and the development of the maritime transport system are the opposite.In 4 ports of Ukraine (Odesa, Kherson, Mariupol, Berdyansk) there was a negative dynamics of cargo turnover, in 3 - positive. Growth occurred at the expense of major ports - Chornomorsk, Pivdennyi, Mykolaiv.Investments in the port infrastructure in the modern world have a geopolitical purpose. The interest of leading actors is concentrated around the geopolitical advantages of the maritime transport system. This is clearly demonstrated by China, which carries out maritime expansion to Europe and builds overseas naval bases.In Ukraine, the dynamics of indicators of marine transport does not correspond to the dynamics of economic indicators. This may indicate the following: the low role of the marine economic complex in shaping the GDP of Ukraine; lack of a unified state approach to the planning of indicators for maritime transport; low level of institutionalization of maritime transport infrastructure.This negatively affects the state of the system of public administration of Ukraine. The processes of realization of the interests of the state in the international arena suffering, the decisive ones being the transport presence on the sea routes. Transit potential of the country is experiencing a difficult period due to armed conflict in the east and the annexation of the Crimea. Existence of problems is expressed in the institutional failure to recognize the strategic importance of the marine presence of Ukraine in the global maritime economic complex. On a complex and extremely tense map of today's geopolitical interests of the world, which tends to bipolarity, Ukraine is practically not represented. The factors of institutional non-recognition are the nature of the «postponed crisis». Weak attention to the issues of direct presence in sea transport corridors negatively affects the systemic efficiency of public administration. This leads to state and interstate geopolitical crises.